Effect of activation atmosphere in the Fischer–Tropsch Synthesis using a “quasi-model” catalyst of γ-Fe2O3 nanoparticles supported on SBA-15 - Perez de Berti, Ignacio Omar (2016)
The effect of different activation atmospheres (CO:H2 or pure H2) on activity and selectivity of iron nanoparticles supported on SBA-15 in Fischer–Tropsch Synthesis, has been studied. To achieve this aim a new preparation method, using monodisperse pre-synthesized γ-Fe2O3 nanoparticles of 3 nm size, supported on SBA-15, was used. These catalysts have structural properties between real and model catalysts. Therefore, they were named “quasi-model” catalysts. Nanoparticles and catalysts were characterized with several techniques: XRD, N2 adsorption at 77 K, magnetic measurements, electron transmission microscopy, Mössbauer spectroscopy between 298 and 13 K in air and controlled atmosphere and thermal gravimetric analysis. Catalytic tests showed clearly that activation with pure H2 leads to a catalyst more active and less selective to methane than that activated with CO:H2. To explain these results, different reduction steps were proposed. These different sequences would produce a diverse number of active sites.